PENDAMPINGAN PEMBUATAN PUPUK ORGANIK CAIR DARI BONGGOL PISANG DAN AIR LERI KEPADA MASYARAKAT DI LEMBANG RANTEDADA - Sallolo Suluh; Widi Kurniawan; Damaris Arrang; Riki Masero; Frans Dedi Dena; Frans Robert Bethony; Chendri Johan; Christof Geraldi Simon; Dennis Lorenzo; Petrus Sampe Lawang; Formanto Paliling; Risa Lasarus; Lery Alfriany Solo; Fikran Fikran; Nofrianto Pasae; Nitha Nitha; Yafet Bontong (Jurnal Abdimas Bina Bangsa, 2024)
Organic farming is increasingly in demand because it prioritizes sustainability and environmentally friendly principles. Liquid organic fertilizer made from banana tubers and leri water is an alternative that is environmentally friendly and easy to produce. However, knowledge and skills in making liquid organic fertilizer still need to be improved among the community, especially in areas such as Lembang Rantedada. This study was carried out through direct assistance and training activities for the community in Lembang Rantedada with a practical and participatory approach, involving the community in every stage of fertilizer production, from raw material preparation to the fermentation and storage process. The result of this mentoring activity is an increase in community knowledge and skills in making liquid organic fertilizer. Communities can use locally available banana stems and water to produce organic fertilizer that is beneficial for their agriculture. Apart from that, awareness is also created about the importance of using organic fertilizer in supporting sustainable agriculture and environmental preservation. Assistance in making liquid organic fertilizer from banana stems and leri water to the community in Lembang Rantedada is an effective step in increasing the independence and sustainability of local agriculture. By increasing knowledge and skills, communities can utilize local resources more optimally and support environmentally friendly agricultural practices